2021
DOI: 10.1002/mar.21559
|View full text |Cite
|
Sign up to set email alerts
|

The atypicality of sustainable luxury products

Abstract: This study tackles the issue of how consumers might perceive luxury products' sustainability-focused communication. We compare consumers' reactions when luxury brands communicate their focus on either product sustainability or product excellence (i.e., a sustainability-vs. excellence-focused communication strategy, respectively). We predict that consumers perceive the former as more atypical for a luxury brand, which renders the communication more effective at enhancing consumers' willingness to buy the brand'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…Some studies have argued that sustainability is incompatible with luxury (Achabou and Dekhili 2013;Davies, Lee and Ahonkhai 2012;Kapferer and Michaut-Denizeau 2014;Voyer and Beckham 2014). Luxury is commonly associated with personal pleasure, complexity, and conspicuousness, while sustainability is related to altruism, sobriety, moderation, and ethics (Amatulli et al, 2020b;Amatulli, De Angelis and Donato 2021;Athwal et al 2019;Batat and Khochman 2022;Naderi and Strutton 2015). However, other studies have shown that sustainability and luxury are a good fit.…”
Section: Luxury and Sustainabilitymentioning
confidence: 99%
“…Some studies have argued that sustainability is incompatible with luxury (Achabou and Dekhili 2013;Davies, Lee and Ahonkhai 2012;Kapferer and Michaut-Denizeau 2014;Voyer and Beckham 2014). Luxury is commonly associated with personal pleasure, complexity, and conspicuousness, while sustainability is related to altruism, sobriety, moderation, and ethics (Amatulli et al, 2020b;Amatulli, De Angelis and Donato 2021;Athwal et al 2019;Batat and Khochman 2022;Naderi and Strutton 2015). However, other studies have shown that sustainability and luxury are a good fit.…”
Section: Luxury and Sustainabilitymentioning
confidence: 99%
“…Because there was no “neutral” point in our measure (not at all charitable–very charitable), we conducted a separate posttest ( n = 99, M _age = 36.28, SD = 10.75; 22.2% female, Amazon Mechanical Turk) to address this concern. We randomly assigned participants to either the sustainable luxury or regular luxury brand condition and asked them to rate whether the brand was “sustainable,” “pro‐environmental,” and “charitable” (Cronbach's α = 0.887; adapted from Amatulli et al, 2021; Septianto et al, 2021), as measured on a 7‐point scale (1 = strongly disagree, 4 = neutral, 7 = strongly agree). As expected, perceived sustainability was higher in the sustainable luxury brand condition than in the regular luxury condition ( M_ regular = 4.10, SD = 1.87 vs. M_ sustainable = 5.53, SD = 0.93, F (1, 97) = 23.12, p < 0.001, η 2 = 0.192).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike luxury brands that focus on prestige as well as high quality, value brands focus on value‐for‐the‐money (Palmeira & Thomas, 2011). As compared with value brands, the price premium that is paid to purchase luxury brands, along with the scarcity message (i.e., special‐edition), makes them a costly signal for status (Amatulli et al, 2021; Hagtvedt & Patrick, 2016; Nelissen & Meijers, 2011). For nonmaterialists, however, we do not have firm predictions regarding the preferences for the different CRM campaigns as a function of luxury versus value brands.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…However, CRM campaigns can pose particular problems for luxury brands because they may represent a conflict between self‐enhancement motivations underlying the consumption of luxury products and self‐transcendence motivations underlying prosocial behavior (Torelli et al, 2012). Although luxury is a subjective concept whose meaning is “specific to a particular time and place” (Belk, 1999, p. 41), it is typically associated with “excess, personal pleasure, superficiality, ostentation, high quality, conspicuousness, and resistance to external normative influence” (Amatulli et al, 2021, p. 1992). Furthermore, a recent study conceptualizes luxury brands as consisting of five dimensions—quality, authenticity, prestige, premium price, and resonance (Ko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%